The answer will be A. 471/11. Hope it help!
Answer:
x=13°
Step-by-step explanation:
If BE is an angle bisector, then it divides the angle into two equal angles. This means that
∠ABE=∠EBC
Since ∠ABE=2x+20 and ∠EBC=4x-6, we have
2x+20=4x-6
2x-4x=-6-20
-2x=-26
2x=26
x=13°
Actually I don't know the answer but what I thing is none of the above.
F(x)=2x^2-x-6
Factoring:
f(x)=2(2x^2-x-6)/2=(2^2x^2-2x-12)/2=[(2x)^2-(2x)-12]/2
f(x)=(2x-4)(2x+3)/2=(2x/2-4/2)(2x+3)→f(x)=(x-2)(2x+3)
g(x)=x^2-4
Factoring
g(x)=[sqrt(x^2)-sqrt(4)][sqrt(x^2)+sqrt(4)]
g(x)=(x-2)(x+2)
f(x)/g(x)=[(x-2)(2x+3)] / [(x-2)(x+2)
Simplifying:
f(x)/g(x)=(2x+3)/(x+2)
Answer: Third Option (2x+3)/(x+2)